Ceramic 'Pot' Water Filters: Investigations into Manufacturing and Performance - Rayner, Justine. (2018)
Abstract: Ceramic 'pot' water filters (CWF) are widely used to improve the microbiological quality of drinking water at the point of use. CWFs are manufactured at >50 filter factories worldwide by pressing a mixture of clay and a burn-out material into the filter shape, which is then fired to a ceramic state. Silver is added during this process as a bactericide. In 2011, the Ceramics Manufacturing Working Group (CMWG) developed recommendations to, "provide guidance to assist filter factories in producing the lowest-cost, most-effective ceramic filters possible". The focus of this dissertation was to further this aim. Specifically, to: 1) investigate the effects of silver type, silver concentration, and input materials on CWF performance; 2) evaluate filter distribution programs; 3) develop a framework for evaluating manufacturing quality control protocols; and 4) synthesize research findings through a systematic literature review. Overall, results suggest that in households filtered water quality meets the low-risk guideline and filter use has been associated with a reduction in diarrheal disease. However, local context, including source water quality, time in use and supply chain access, likely influence long-term filter use and can affect in situ technology performance evaluation. Results from laboratory investigations and the systematic review demonstrate filters can achieve ≥2 log reduction in bacteria; however, silver should not be relied on as a principal treatment mechanism for long-term filter performance. Thus, it is recommended that filters be tested for bacteria removal prior to silver application. Burn-out material particle size and clay content (<2µm) are associated with bacteria removal by the porous matrix. Lastly, with participation from factories, a framework for evaluating quality control protocols was developed. CWFs are widely manufactured, promoted and used; thus, there is a need to continue supporting factories in manufacturing high-quality filters and to broadly disseminate research findings.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Civil Engineering.; Advisor: Daniele Lantagne.; Committee: David Gute, Derek Chitwood, and Kishore Pochampally.; Keyword: Environmental engineering.